Pengalaman Pasien Covid-19 yang Menjalani Perawatan di Rumah Sakit Darurat Covid Wisma Atlet Jakarta - Diana Ekawaty (Jurnal Keperawatan Silampari, 2021)
This study aims to explore the experiences of COVID-19 patients treated at the Wisma Atlet COVID-19 Emergency Hospital. The research method used in this study is a qualitative research method with thematic analysis methods. This study showed that there were 2 participants with suspected cases and 5 participants with confirmed cases, while the age of participants was between 26 to 54 years. The participants' occupations are four employees, two medical personnel, and one civil servant with an average quarantine time of 14 to 38 days of care. In conclusion, This study resulted in 6 themes, namely: changes experienced by patients when diagnosed with COVID-19, changes experienced by the family and environment of family members diagnosed with COVID-19, sources of information for treatment, attitudes of health workers who carry out treatment, description of patient feelings. while being treated, the hope of COVID-19 patients being treated at the Wisma Atlet RSDC. Keywords: COVID-19, Wisma Athlete Jakarta Emergency Hospital, Quarantine, Experience